Evaluation of Accounting Information Systems Using the PIECES Method at Hotels in Bali - Sukraeni, Dewa Ayu Made Rai; Arnawa, I Putu; Rukmiyati, Ni Made Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to evaluate the Accounting Information System (AIS) by identifying the extent to which the AIS is in preparing financial statements. The method used in this study is a quantitative descriptive method by applying the PIECES model (Performance, Information, Economics, Control, Efficiency, and Service) where each PIECES variable is a reference for evaluation and analysis of information systems. Data collection was carried out by distributing questionnaires and data processing analysis was carried out using a Likert scale. The sample of this study was Finance, FB, and FO staff with a total of 30 respondents. Data was measured using a Likert scale. The results of this study stated that the 6 PIECES variables had an average value, namely Performance (4.62), Information (4.54), Economics (4.46), Control (5.00), Efficiency (4.70) and Service (4.78). The conclusion of the results of this study stated that the implementation of AIS when reviewed with PIECES analysis is good, effective, efficient in producing financial statements as evidenced by the level of satisfaction of each variable entering the SATISFIED category. This research using the PIECES method can provide management with an overview to evaluate AIS to assess and improve the aspects of AIS used